Development of Deep Learning-based Instructional Module for Enhancing Critical Thinking in Pancasila Learning - Anggrayni, M.; Asmaryadi, Ahmad Ilham; Susilawati, Wiwik Okta (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a deep learning-based instructional module for enhancing critical thinking in Pancasila education at the elementary level. The Research and Development (R&D) method was employed, using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, document analysis, and surveys, with a particular emphasis on the dimensions of validity, practicality, and effectiveness as the core framework for the data analysis technique. The module demonstrated high validity, with expert evaluations rating it "very valid" in terms of content, visual design, and language use. Validator input improved the module's alignment with student characteristics. Teachers reported ease of implementation and responsiveness to learners' needs, with an average practicality score of 93.3%. The module was effective in enhancing students' critical thinking, with 63.16% of students scoring 90-100 and an overall effectiveness score of 82.2%. These findings highlight the potential of deep learning to foster knowledge acquisition, conceptual understanding, practical skills, and active learner engagement. The developed module is a strategic innovation aligned with the Merdeka Curriculum and responsive to 21st-century education challenges.